Unconventional Monetary Policies in Emerging Markets and Frontier Countries. (IMF Working Papers; Working Paper ;, 2021)
The COVID-19 crisis induced an unprecedented launch of unconventional monetary policy through asset purchase programs (APPs) by emerging market and developing economies. This paper presents a new dataset of APP announcements and implementation from March until August 2020 for 27 emerging markets and 8 small advanced economies. APPs' effects on bond yields, exchange rates, equities, and debt spreads are estimated using different methodologies. The results confirm that APPs were successful in significantly reducing bond yields in EMDEs, and these effects were stronger than those of policy rate cuts, suggesting that such UMP could be important tools for EMDEs during financial market stress.